Drivers and Limitations of the Indian Startup Industry - M. S. Reshchikova (Vestnik MGIMO-Universiteta, 2023)
This paper addresses the effectiveness of a state-supported startup ecosystem in India in the context of economic and social development challenges. By conducting a detailed study of Indian entrepreneurs, investors, and relevant government documents pertaining to startup ecosystem development programs, as well as reports from research and analytical centers providing key industry indicators, the author concludes that the current startup ecosystem in India, despite several achievements, lacks effectiveness due to persistent challenges of administrative and regulatory nature, as well as socio-economic factors. The unprecedented growth witnessed in this sector in 2021 has highlighted existing problems, demonstrating the inability to establish a sustainable support mechanism for startups while disregarding the limitations that hinder the entrepreneurial and consumer potential of the Indian economy. The findings of this research showcase the immense potential of the Indian startup industry, which undoubtedly serves as a driving force for economic development in India, despite its vulnerability to certain elements. The experiences of India, including the challenges encountered in building a robust startup ecosystem, can provide valuable insights for other countries such as Russia.